Microbiologically influenced stress corrosion cracking responsible for catastrophic failure of cable bolts. (January 2022) - Chen, Honghao; Kimyon, Önder; Ramandi, Hamed Lamei; Craig, Peter; Gunawan, Cindy; Wu, Saisai; Manefield, Mike; Crosky, Alan; Saydam, Serkan
Highlights: HISCC is produced by the action of sulphur- and sulphate-reducing bacteria. The role of the microorganisms in HISCC is the generation of H2 S that promotes hydrogen entry into the steel. Underground environments rich in sulphate, organic matters, and with a low water refreshment rate are ideal for MISCC. Abstract: In the past two decades, reports of the premature failure of cable bolts used in the mining and civil industries have been increasing. Previous studies have established that failure occurs through hydrogen-induced stress corrosion cracking (HISCC), which is a type of environmentally assisted hydrogen cracking. However, to date, the cause of HISCC has been unclear. For the first time, we studied the role of microorganisms in the failure of cable bolts using components present in SCC-affected mines. Stressed coupons were prepared from the cable bolt wires and tested in groundwater with additions of sulphate-reducing bacteria, coal, clay, pyrite and lactate. It was found that hydrogen sulphide (H2 S) produced by sulphate- and sulphur-reducing bacteria promoted hydrogen diffusion into the steel and, in the presence of stress, caused HISCC. This suggests that control of H2 S production should be a priority for mining and civil industries to avoid premature failure of anchoring systems.